Penggunaan Dental Laser Pada Eksisi Irritation Fibroma - I Gusti Ayu Ari Widiastuti (School of Dentistry Faculty of Medicine Udayana University, 2017)
The utilization of laser technology is now very numerous and widespread in human life. Laser is an electromagnetic wave that can interact with biological tissue with side effects depend on the power and the exposure received by the biological tissue. Lasers are typically used in the field of dentistry known as the dental laser. According to the use of dental lasers can be used for hard tissue, soft tissue and low-level light (LLLT). The use of dental laser indicated for many surgical procedures, such as surgical procedures endodontics, periodontics, surgery to bone for implant placement. Lasers can also be used to carry out the preparation, incision, excision, and Contouring until excision of soft tissue irritation fibroma. Irritation fibroma is a benign lesion that is most often found in the oral cavity. Bites on the buccal mucosa and lips as well as irritation from the use of denture is a common cause of this lesion. The purpose of this paper is to add information about the various dental lasers and how dental laser for excision of irritation fibroma and benefits for patients.